KIMYONI O‘QITISHDA RAQAMLI TEXNOLOGIYALAR - Ajieva, M.B.; Begmanova, G.; Naurizbaeva, T. (SCIENCE and SOCIETY, 2024)
This article provides concepts about the importance of pedagogy in teaching chemistry, educational technologies, the importance of educational technologies in teaching chemistry, digital and cloud technologies, the use of digital technologies in education, the tools and advantages of digital technologies.
Keywords: pedagogy; educational technologies; chemistry; digital and cloud technologies; digital technologies in education